Budget of Tropospheric Ozone in Africa : what the AMMA-Chemistry program brought - (:unkn) unknown (My University, 2009)
This PhD thesis took place in the frame of the international program AMMA (African Monsoon Multidisciplinary Analysis) which aims to better document, understand and forecast the west african monsoon and its variability. The ozone distribution in a altitude-latitude cross section has been simulated using an idealized 2D model in order to assess which processes contribute to the establishment of the meridional ozone gradients as observed by MOZAIC and AMMA airborne measurements. A second part of this work has been dedicated to the analysis of the ozone sounding data set over Cotonou, Bénin. The seasonnal and interannual variations of the ozone vertical distribution are highlighted. Modeling studies using chemistry transport models and a lagrangian particle dispersion model investigate the inter hemispheric transport of biomass burning pollution during the boreal summer.
Keywords: African Research